Analisis Manajemen Risiko Pada Proyek Konstruksi Jalan di Provinsi Jambi - Handayani, Elvira; Zulfiati, Ria; Tsani, Mohammad Alwi Ibrohim (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
In the implementation of road construction projects, there are often various obstacles that arise due to the risks that occur which result in not achieving the expected performance, quality and achievement of work results. The purpose of this study was to determine the risk factors that affect the implementation of work in the field and to determine the application of risk management in road construction projects. In this study, risk identification, risk analysis and risk response were carried out in the construction of road construction projects, especially road construction in Jambi Province. The research method used was by way of a survey distributing risk factor questionnaires and actions on risk factors to consultants. The assessment method uses a risk matrix assessment sourced from AS/NZS 4360: 2004. From the results of this study, it is found that the risk level for road construction work in Jambi Province is very high risk (very high) of 8%, high risk (High) of 7%, and a moderate risk of (Medium) of 16%.